Sartono Kartodirdjo and Kuntowijoyo in Indonesian History Methodology - Sugeng Priyadi (Paramita: Historical Studies Journal, 2026)
Abstract: This article compares the methodological ideas of Sartono Kartodirdjo and Kuntowijoyo. Using the historical method, it treats their major works as historical documents examined through heuristics, criticism, interpretation, and historiography. Kartodirdjo emphasizes inductive logic grounded in historical facts and supported by social science approaches, including economics, sociology, political science, anthropology, geography, and social psychology. This multidimensional framework became an important legacy and opened wider possibilities for historical research in Indonesia. In contrast, Kuntowijoyo encourages young historians to develop thematic historical methodologies as fields of specialization. His methodological thinking begins with historiography as the outcome of research, which then serves as the basis for broader, more comprehensive methodological reflections. He also explains historical methodology by using auxiliary sciences to interpret historical phenomena. In Indonesian historical practice, method and methodology are inseparable, since historical inquiry requires both inductive reasoning based on facts and deductive reasoning based on theory. Supported by auxiliary sciences and grounded in research, the combination of these two logics can produce richer, more comprehensive historiography. This study contributes to historiographical discourse by clarifying the distinction between methodology and method and by underlining the need for a more integrative and multidimensional framework in contemporary Indonesian historical research.   Abstrak: Artikel ini membandingkan gagasan metodologis Sartono Kartodirdjo dan Kuntowijoyo. Dengan menggunakan metode sejarah, karya-karya utama keduanya diposisikan sebagai dokumen historis yang dianalisis melalui tahapan heuristik, kritik, interpretasi, dan historiografi. Kartodirdjo menekankan logika induktif yang berlandaskan fakta sejarah serta didukung oleh pendekatan ilmu-ilmu sosial, seperti ekonomi, sosiologi, ilmu politik, antropologi, geografi, dan psikologi sosial. Kerangka multidimensional ini menjadi warisan penting sekaligus membuka peluang yang lebih luas bagi penelitian sejarah di Indonesia. Sebaliknya, Kuntowijoyo mendorong sejarawan muda untuk mengembangkan metodologi sejarah tematik sebagai bidang spesialisasi. Pemikiran metodologisnya berangkat dari historiografi sebagai hasil penelitian, yang kemudian menjadi dasar dalam merumuskan refleksi metodologis yang lebih luas dan komprehensif. Ia juga menjelaskan metodologi sejarah melalui pemanfaatan ilmu-ilmu bantu dalam menafsirkan fenomena sejarah. Dalam praktik sejarah di Indonesia, metode tidak dapat dipisahkan dari metodologi, karena kajian sejarah memerlukan integrasi antara penalaran induktif berbasis fakta dan penalaran deduktif berbasis teori. Didukung oleh ilmu-ilmu bantu dan pendekatan grounded research, kombinasi kedua logika ini mampu menghasilkan historiografi yang lebih kaya dan komprehensif. Penelitian ini berkontribusi dalam memperjelas perbedaan konseptual antara metodologi dan metode, serta menegaskan pentingnya kerangka yang lebih integratif dan multidimensional dalam penelitian sejarah kontemporer di Indonesia.